Antena Mikrostrip Rectangular dengan Slot Rectangular 2,45 Dan 5,85 Ghz Menggunakan Tekstil Fleece Untuk Telemedis - Fadilla Melania Rachmaputri (Jurnal Teknika, 2021)
Telemedicine is one of the technologies used for long-distance health services with wireless communication in the human body. This research is designing an antenna for telemedicine, namely a wearable antenna. The selection of textile materials used is a good choice for telemedicine because it has a relatively small size, can be bent, and comfortable to be used. This final project is designing a rectangular microstrip antenna with a dual-band rectangular slot in the ISM range of 2.45 and 5.85 GHz with a feed-line. The measurement results on the condition on the body for the frequency of 2.45 GHz are the gain value of 5.45 dB, VSWR of 1.4550, and the bandwidth of 180 MHz. For 5.85 GHz the gain value is 5.11 dB, VSWR is 1.5082, and the bandwidth is 260 MHz. The resulting radiation pattern is unidirectional.